Szczepkamyces quercicola sp. nov. (Polyporales, Basidiomycota) evidenced by morphological characters and molecular phylogeny - Zhou, Meng; Dai, Yu-Cheng; Yuan, Yuan (Phytotaxa, 2022)
Szczepkamyces, typified by Szczepkamyces campestris, was a monotypic genus. Based on distinct morphological characters and phylogeny inferred from the combined 2-locus dataset [ITS1-5.8S-ITS2 (ITS) + nuclear large subunit RNA (nLSU)], another species of the genus, Szczepkamyces quercicola sp. nov., is confirmed. It is characterized by annual, resupinate, yellowish basidiocarps with big pores, a dimitic hyphal structure, generative hyphae with clamp connections, indextrinoid skeletal hyphae, the absence of hyphal pegs, the presence of dendrohyphidia, cylindrical basidiospores measuring 15–17.5 × 5–6 µm, and growth on Quercus in boreal forests in east Himalayas. Morphologically S. quercicola resembles Megasporoporia sensu lato, but phylogenetically it is closely related to S. campestris. The differences between S. quercicola and its similar or related species are discussed.